KONSTRUKSI SOSIAL ORANG TUA TENTANG PENDIDIKAN DAN POLA ASUH ANAK USIA DINI DI KALANGAN BURUH PABRIK ROKOK DI KECAMATAN MEJOBO KABUPATEN KUDUS - Diah Ayu Mawarti (JURNAL LENTERA ANAK, 2021)
This researct aims to examine the social construction of older children in the family education cigarette factory workers in District Mejobo Kudus, parenting practiced by cigarette workers’ family to their children, the impact of parenting practiced by the cigarette workers families on children's social behavior. To achieve the focuses of this researched, qualitatif method was applied. The subjects were 9 cigarette workers’ family. Data was collected using interviews, participant observation and document study. The results showed, the social construction of older people in the family about the child's education in the District of cigarette factory workers Mejobo varied among others: a faith-based education to interpret education as prestige, media to get a job, as a tradition, and faith-based education is not as neutrality. Parenting practiced by families cigarette factory workers in the District of Kudus Mejobo among other authoritarian parenting, democratic, and permissive (3) The impact of parenting practiced by families cigarette workers factory form the social behavior of children.